CORAL UNIVERSITÁRIO: CONQUISTAS DE UM PROJETO TEMÁTICO NA ÓTICA DOS PARTICIPANTES - Buchmann, Letícia T.; Wildner, Laura E. S.; Rein, Andressa W.; Rosinke, Darlene J. (Salão do Conhecimento, 2013)
Resumo